Proposal for the implementation of good manufacturing practices (bpm) in the "francisco navas" pasteurized orange juice plant in the city of guayaquil - Molina Bravo, Grace Helga; Pibaque Banchón, Jesús Darío (Ingeniería Química y Desarrollo, 2024)
One of the aspects that has been developed on a large scale in recent years is quality management, as organizations have understood their social responsibility in the face of an increasingly informed and demanding society. It is under this approach that the present study tried to know what the situation was in an orange juice processing plant in the city of Guayaquil, observing deficiencies in its production process, making a comparative analysis, and questioning suppliers about the quality of the juice. product that they deliver to the plant, that is, a study was carried out of all those phases that affect the quality of the product, understanding that a product with higher quality implies the satisfaction of the final customer and therefore an improvement in the profitability of the organization.  This project suggests a guide to implement good manufacturing practices for the development of the juice processing stages, making effective the improvement of its production processes and optimization of resources, which due to management negligence have not been applied, violating the current regulations that stipulate that all food processing plants must base their processes on good manufacturing practices as a tool for handling and manipulating food products.
Keywords: restructuring; production; safety